Complex Training: Efektifitas Latihan Dalam Meningkatkan Power Otot Pada Atlet Bola Voli Remaja - Arif Hidayat; Riyan Pratama; M. Fransazeli Makorohim (Journal Sport Area, 2020)
Complex training is an exercise method that combines plyometrics with strength training. This exercise is an exercise used to increase muscle power. This study aims to determine the effect of training of complex training methods towards leg muscle power and arm muscle power for adolescent volleyball athletes. The method used in this study is an experiment with a control group pretest - post test design. Subjects in this study are 23 adolescent volleyball athletes (14-17 years old) with 12 males and 11 females, who are divided into two groups of experimental groups (n = 12) and control groups (n = 11) with randomized matched pair design based on the ranking of the vertical jump ability. Instrument used in this study is vertical jump test (leg power) and the medicine ball throw test (arm power). The data analysis technique uses the paired t-test with a significance level of α = 0.05. The results show that training using a complex training method provides a good benefit in improving leg and arm muscle power. Therefore, this method is appropriate for used by adolescent volleyball athletes that have had experience of weight training in improving muscle power towards adolescent volleyball athletes